Preliminary study on factors affecting E-commerce success: a modified Delone and McLean model - Ali, Najma Imtaiz; Samsuri, Suhaila; Brohi, Imtiaz Ali; Soomro, Arjumand Bano; Soomro, Saira; Shah, Asadullah (Institute of Electrical and Electronics Engineers Inc., 2018)
Electronic commerce has gained the popularity since last two decades, due to its recompenses towards the online transactions. Academicians and e-retailers eagerly want to identify the factors which affect the e-commerce success. The main intention of this study to investigate the factors which are essential to draw the net benefits of e-commerce from an individual perspective rather than the organization perspective. The proposed framework in this paper is based on Mclean and Delone 2003 IS success model along with two extra variables that are privacy and trust. In this paper, the author discussed the result of the pilot study. The authors designed the quantitative research questionnaire by adopting the items from the previous studies and conducted the pilot study to check the reliability of the questionnaire. The overall value for Cronbach's alpha was 0.89 and also the Cronbach's alpha value for individual constructs were greater than 0.7, which indicates that there is a strong relation between the items. This research engrossed on four factors that are system quality, service quality, privacy, trust, that are essential for achieving the user satisfaction which in turn leads to achieve the e-commerce net benefits. In addition to service quality and system quality, trust and privacy are the important factors that affect the net benefits through user satisfaction, hence the modified version of Delone and Mclean IS success model from individual perspective is proposed.